Prognostic value of inflammatory markers for detecting anastomotic leakage after esophageal resection - Liesenfeld, Lukas; Sauer, Peter; Diener, Markus K.; Hinz, Ulf; Schmidt, Thomas; Müller, Beat P.; Hackert, Thilo; Büchler, Markus W.; Schaible, Anja (BMC surgery, 2020)
Early diagnosis of anastomotic leakage (AL) after esophageal resection is crucial for the successful management of this complication. Inflammatory serological markers are indicators of complications during the postoperative course. The aim of the present study was to evaluate the prognostic value of routine inflammatory markers to predict anastomotic leakage after transthoracic esophageal resection.
Gesehen am 15.01.2021